Jesuits and the natural sciences in modern times, 1814-2014 - Udías Vallina, Agustín (Brill research perspectives in Jesuit studies, 2019)
After their restoration of 1814, the Jesuits made significant contributions to the natural sciences, especially in the fields of astronomy, meteorology, seismology, terrestrial magnetism, mathematics, and biology. This narrative provides a history of the Jesuit institutions in which these discoveries were made, many of which were established in countries that previously had no scientific institutions whatsoever, thus generating a scientific and educational legacy that endures to this day. The article also focuses on the teaching and research that took place at Jesuit universities and secondary schools, as well as the order?s creation of a worldwide network of seventy-four astronomical and geophysical observatories where particularly important contributions were made to the fields of terrestrial magnetism, microseisms, tropical hurricanes, and botany.0